Erasmus and Calvin on the Foolishness of God : Reason and Emotion in the Christian Philosophy - Essary, Kirk (Toronto : University of Toronto Press, 2017)
What did Paul mean when he wrote that the foolishness of God is wiser than human wisdom? Through close analysis of the sixteenth-century reception of Paul's discourses of folly, this book examines the role of the New Testament in the development of what Erasmus and John Calvin refer to as the Christian philosophy. Erasmus and Calvin on the Foolishness of God reveals the importance of Pauline rhetoric in the development of humanist critiques of scholasticism while charting the formation of a specifically affective approach to religious epistemology and theological method. As the first book-length examination of Calvin's indebtedness to Erasmus, which also considers the participation of Bullinger, Pellikan, and Melanchthon in an Erasmian exegetical milieu, it is a case study in the complicated cross-confessional exchange of ideas in the sixteenth century. Kirk Essary examines assumptions about the very nature of theology in the sixteenth century, how it was understood by leading humanist reformers, and how ideas about philosophy and rhetoric were received, appropriated, and shared in a complex intellectual and religious context.
Frontmatter -- Contents -- Acknowledgments -- List of Abbreviations and Early Modern Editions -- Preface -- 1. Calvin s Erasmus, Theologia Rhetorica , and Pauline Folly -- 2. Foolishness as Religious Knowledge -- 3. Hidden Wisdom and the Revelation of the Spirit -- 4. Milk for Babes: A Pauline Eloquence -- 5. Blaming Philosophy, Praising Folly -- 6. The Affective Christian Philosophy -- Conclusion -- Notes -- Bibliography -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Jul 2017)
Keywords: Christian philosophy -- History -- 16th century; Theology -- History -- 16th century; DISCOUNT-B.